2018
DOI: 10.3892/ijmm.2018.3496
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from human umbilical cord mesenchymal stem cells improve myocardial repair via upregulation of Smad7

Abstract: It has been previously reported that exosomes derived from human umbilical cord mesenchymal stem cells (hucMSC)‑exosomes exhibit cardioprotective effects on the rat acute myocardial infarction (AMI) models and cardiomyocyte hypoxia injury models in vitro, however the exact mechanisms involved require further investigation. The present study aimed to investigate the repair effects of hucMSC‑exosomes on myocardial injury via the regulation of mothers against decapentaplegic homolog 7 (Smad7) expression. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 33 publications
1
36
0
1
Order By: Relevance
“…In recent years, increasing studies provided strong evidence that MSC-Exos involve in damage repair process by delivering functional proteins or RNAs. For example, Wang et al [24] showed that exosomes derived from human umbilical cord MSCs improved myocardial repair via Smad7 upregulation. Tao et al [25] observed that exosomes derived from miR-140-5p-overexpressing synovial MSCs promoted the proliferation and migration of rat chondrocytes, which in turn ameliorated OA.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing studies provided strong evidence that MSC-Exos involve in damage repair process by delivering functional proteins or RNAs. For example, Wang et al [24] showed that exosomes derived from human umbilical cord MSCs improved myocardial repair via Smad7 upregulation. Tao et al [25] observed that exosomes derived from miR-140-5p-overexpressing synovial MSCs promoted the proliferation and migration of rat chondrocytes, which in turn ameliorated OA.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are cell-derived vesicles that transport proteins, lipids, DNA, and RNA and are involved in signal transduction, immune responses, antigen presentation, and would healing among other cellular processes [11], indicating their potential in bioactive therapies. In fact, hucMSC-derived exosomes have been shown to exert cardioprotective effects [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…UC-MSC-EVs have also been indicated to provide pro-proliferative effect in cells residing in border zone area of infarcted myocardium, as shown in rat models of AMI in vivo by increased level of Ki67 indicating cardiac cell proliferation [53]. A study conducted by Wang et al revealed that EVs from UC-MSCs enhance Smad7 expression via inhibiting its impeditory miR-125b-5p, which eventually resulted in decline in myocardial cells apoptosis and injury [54]. Interestingly, study from Liu and colleagues suggests that UC-MSC-EVs may also regulate autophagy in cardiac cells by activating PI3K/AKT/mTOR signaling pathway leading to inhibition of heart cells apoptosis in rat model [55].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%